Radiation dose of digital radiography (DR) versus micro-dose x-ray (EOS) on patients with adolescent idiopathic scoliosis: 2016 SOSORT- IRSSD "John Sevastic Award" Winner in Imaging Research. Issue 1 (December 2016) - Hui, Steve; Pialasse, Jean-Philippe; Wong, Judy; Lam, Tsz-ping; Ng, Bobby; Cheng, Jack; Chu, Winnie
Abstract Background Patients with adolescent idiopathic scoliosis (AIS) frequently receive x-ray imaging at diagnosis and subsequent follow monitoring. The ionizing radiation exposure has accumulated through their development stage and the effect of radiation to this young vulnerable group of patients is uncertain. To achieve the ALARA (as low as reasonably achievable) concept of radiation dose in medical imaging, a slot-scanning x-ray technique by the EOS system has been adopted and the radiation dose using micro-dose protocol was compared with the standard digital radiography on patients with AIS. Methods Ninety-nine participants with AIS underwent micro-dose EOS and 33 underwent standard digital radiography (DR) for imaging of the whole spine. Entrance-skin dose was measured using thermoluminescent dosimeters (TLD) at three regions (i.e. dorsal sites at the level of sternal notch, nipple line, symphysis pubis). Effective dose and organ dose were calculated by simulation using PCXMC 2.0. Data from two x-ray systems were compared using independent-samples t-test and significance level at 0.05. All TLD measurements were conducted on PA projection only. Image quality was also assessed by two raters using Cobb angle measurement and a set of imaging parameters for optimization purposes. Results Entrance-skin dose from micro-dose EOS system was 5.9–27.0 times lower at various regions compared with standard DR. The calculated effective dose was 2.6 ± 0.5 (μSv) and 67.5 ± 23.3 (μSv) from micro-dose and standard DR, respectively. The reduction in the micro-dose was approximately 26 times. Organ doses at thyroid, lung and gonad regions were significantly lower in micro-dose (p  < 0.001). Data were further compared within the different gender groups. Females received significantly higher (p  < 0.001) organ dose at ovaries compared to the testes in males. Patients with AIS received approximately 16–34 times lesser organ dose from micro-dose x-ray as compared with the standard DR. There was no significant difference in overall rating of imaging quality between EOS and DR. Micro-dose protocol provided enough quality to perform consistent measurement on Cobb angle. Conclusions Entrance-skin dose, effective dose and organ dose were significantly reduced in micro-dose x-ray. The effective dose of a single micro-dose x-ray (2.6 μSv) was less than a day of background radiation. As AIS patients require periodic x-ray follow up for surveillance of curve progression, clinical use of micro-dose x-ray system is beneficial for these young patients to reduce the intake of ionizing radiation.